2023
DOI: 10.1186/s13018-023-03647-2
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence-based informed consent form for total knee arthroplasty

Abstract: Introduction Informed consent documentation is often the first area of interest for lawyers and insurers when a medico-legal malpractice suit is concerned. However, there is a lack of uniformity and standard procedure about obtaining informed consent for total knee arthroplasty (TKA). We developed a solution for this need for a pre-designed, evidence-based informed consent form for patients undergoing TKA. Materials and methods We extensively revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…It also acts as a medicolegal document that often becomes the crux of many malpractice claims [ 41 ]. It is mandated as per the law that patients be informed about the basic steps and course of the surgical procedure they are proposed to undergo [ 42 ]. Hence, it is mandatory that, if a patient is planning to undergo robotic surgery, their consent for the use of the robot be obtained beforehand.…”
Section: Reviewmentioning
confidence: 99%
“…It also acts as a medicolegal document that often becomes the crux of many malpractice claims [ 41 ]. It is mandated as per the law that patients be informed about the basic steps and course of the surgical procedure they are proposed to undergo [ 42 ]. Hence, it is mandatory that, if a patient is planning to undergo robotic surgery, their consent for the use of the robot be obtained beforehand.…”
Section: Reviewmentioning
confidence: 99%
“…17,18 Several developments have taken place over the last decades that have truly altered the way we look at TKA today. [19][20][21] Some of the fascinating aspects will be presented and discussed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Nicola Maffulli.…”
mentioning
confidence: 99%